Synthesis of 4,5-Disubstituted Methyl 1H-Pyrrole-2-carboxylates from 3-Chloroacrylaldehydes and Hippuric Acid - Samsonenko, Anna L.; Kostyuchenko, Anastasia S.; Zheleznova, Tatyana Yu.; Shuvalov, Vladislav Yu.; Uliankin, Evgenii B.; Shatsauskas, Anton L.; Fisyuk, Alexander S. (Synthesis, 2024)
The Vilsmeier–Haack reaction of ketones with DMF and POCl3 produced 3-chloroacrylcarbaldehydes, which were converted into the corresponding (Z)-4-[(Z)- or (Z)-4-[(E)-3-chloroallylidene)-2-phenyloxazol-5(4H)-ones] (azlactones) or their isomeric mixtures when heated with hippuric acid in propionic anhydride. It was shown that the alcoholysis products of these compounds, resulting from the opening of the oxazolone ring, undergo copper-catalyzed intramolecular cross-coupling reactions with the formation of methyl 1H-pyrrole-2-carboxylates. Thus, a one-pot method was developed for the synthesis of methyl 1H-pyrrole-2-carboxylates starting from 4-(3-chloroallylidene)-2-phenyloxazol-5(4H)-ones.
Keywords: conjugation; cyclization; heterocycles; pyrroles; catalysis; copper